2010
DOI: 10.1089/jmf.2009.0117
|View full text |Cite
|
Sign up to set email alerts
|

Essential Oil of Thymus capitatus Hoff. et Link. from Matmata, Tunisia: Gas Chromatography-Mass Spectrometry Analysis and Antimicrobial and Antioxidant Activities

Abstract: Thymus capitatus Hoff. et Link. essential oil was constituted by thymol (89.06%) as a major component followed by p-cimene (5.04%) and γ-terpinene (3.19%) after analysis by gas chromatography-flame ionization detection and gas chromatography-mass spectrometry. The antioxidant activity assays of the essential oil used in the inhibition of the radical cation 2,2'-azinobis(3-ethylbenzothiazoline-6-sulfonate) and the free radical 2,2-diphenyl-1-picrylhydrazyl showed high 50% inhibitory concentration values of 1.24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
15
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(21 citation statements)
references
References 25 publications
5
15
1
Order By: Relevance
“…In contrast, rosmarinic acid was found to be a minor compound in AE (Table 1). These findings are in accordance with those reported in previous studies on T. capitata from South Tunisia and other countries [14,19]. Mkaddem et al [19] showed that the major EO compound in T. capitata was thymol, using plants from the same region.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, rosmarinic acid was found to be a minor compound in AE (Table 1). These findings are in accordance with those reported in previous studies on T. capitata from South Tunisia and other countries [14,19]. Mkaddem et al [19] showed that the major EO compound in T. capitata was thymol, using plants from the same region.…”
Section: Discussionsupporting
confidence: 92%
“…These findings are in accordance with those reported in previous studies on T. capitata from South Tunisia and other countries [14,19]. Mkaddem et al [19] showed that the major EO compound in T. capitata was thymol, using plants from the same region. Also, Behravan et al [14] showed that thymol and carvacrol were the major compounds in T. capitata EO from Iran.…”
Section: Discussionsupporting
confidence: 92%
“…Only phenolics presented a satisfactory correlation with the DPPH assay ( R 2 = 0.73, respectively). As reported in previous studies, the antioxidant activity of EOs was related to their phenolic contents (Ennajar and others 2009; Mkaddem and others 2010), hydrocarbons monoterpene (Chabir and others 2011), and sesquiterpenes compounds (Mukazayire and others 2011). …”
Section: Resultssupporting
confidence: 58%
“…The demand for essential oils from these species is increasing for perfumery, cosmetic and medicinal applications (Hazzit et al, 2009). Thymes are well known for their antispasmodic, sedative, antioxidant (Safaei-Ghomi, Ebrahimabadi, Djafari-Bidgoli, & Batooli, 2009;Mkaddem et al, 2011), antimicrobial (Hazzit et al, 2009;Mkaddem et al, 2011), antifungal (Giordani, Hadef, & Kaloustian, 2008), antibacterial (Bhaskara, Angers, Gosselin, & Arul, 1998) and antiaflatoxinogenic (Razzaghi-Abyaneh et al, 2009) properties. In traditional medicine, infusions, leaves and flowers decoctions were used as tonic, anti-inflammatory, antiparasitic, antitussive and carminative (Stahl-Biskup & Sá ez, 2002).…”
Section: Introductionmentioning
confidence: 99%